Toll‐Like Receptor (TLR)4 and MyD88 are Essential for Atheroprotection by Peritoneal B1a B Cells. Issue 11 (November 2016) - Hosseini, Hamid; Li, Yi; Kanellakis, Peter; Tay, Christopher; Cao, Anh; Liu, Edgar; Peter, Karlheinz; Tipping, Peter; Toh, Ban‐Hock; Bobik, Alex; Kyaw, Tin
Abstract : Background: We previously identified peritoneal B1a cells that secrete natural IgM as a key atheroprotective B cell subset. However, the molecules that activate atheroprotective B1a cells are unknown. Here, we investigated whether Toll‐like receptors (TLRs) TLR2, TLR4, and TLR9 expressed by B1a cells are required for IgM‐mediated atheroprotection. Methods and Results: We adoptively transferred B1a cells from wild‐type mice or from mice deficient in TLR2, TLR4, TLR9, or myeloid differentiation primary response 88 (MyD88) into ApoE −/− mice depleted of peritoneal B1a cells by splenectomy and fed a high‐fat diet for 8 weeks. Elevations in plasma total, anti‐oxLDL (oxidized low‐density lipoprotein), anti‐leukocyte, anti‐CD3, anti‐CD8, and anti‐CD4 IgMs in atherosclerotic mice required B1a cells expressing TLR4 and MyD88, indicating a critical role for TLR4‐MyD88 signaling for IgM secretion. Suppression of atherosclerosis was also critically dependent on B1a cells expressing TLR4‐MyD88. Atherosclerosis suppression was associated not only with reductions in lesion apoptotic cells, necrotic cores, and oxLDL, but also with reduced lesion CD4 + and CD8 + T cells. Transforming growth factor beta 1 (TGF‐β1) expression, including macrophages expressing TGF‐β1, was increased, consistent with increased IgM‐mediated phagocytosis of apoptotic cells by macrophages. Reductions in lesion inflammatory cytokines tumor necrosis factor alpha (TNF‐α), interleukin (IL) 1β, and IL‐18 were consistent with augmented TGF‐β1 expression. Conclusions: TLR4‐MyD88 expression on B1a cells is critical for their IgM‐dependent atheroprotection that not only reduced lesion apoptotic cells and necrotic cores, but also decreased CD4 and CD8 T‐cell infiltrates and augmented TGF‐β1 expression accompanied by reduced lesion inflammatory cytokines TNF‐α, IL‐1β, and IL‐18.